GAMBARAN TINGKAT PENGETAHUAN DAN PENGALAMAN WANITA MENOPAUSE MENGHADAPI HOT FLASHES - Nisa Marini Nabila; Erika Erika; Sri Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Menopause is natural process that occurs in everry woman. One of the signs of physical symptoms during menopause is hot flashes. Hot flashes is a feeling of heat, burning that occurs in the face, neck, chest, and even throught the body, which is accompanied by sweat, heart palpitations varying time span for each menopausal woman. Design research sed is descriptive quantitative research. The sample are 97 respondents taken based on the inclusion criteria using purposivve sampling technique. Measuring devices used are the questionare of respondents characteristic, questtionare of level knowledge and questionare experience. The analysis used the univariate analysis to know the distribution of respondents characteristic, level of knowledge and experience. The results of study showed the most respondents ages are 50-54 years old as much 52 people (53,6%), 93 people (95,9%) had islam religion, 49 people (50,5%) had minang tribe, 46 people (47,4%) were middle education (senior high school), 71 people (73,2%) respondents not work, 77 people (79,4%) married, 67 people (69,1%) respondents had first menstruation at the age 10-14 years old, and had the last menstrual period at the age 50-54 years as much 48 people (49,5%). For 97 respondents there were has level of enough knowledge 38 people (39,2%), good knowledge 33 people (34,0%), and 26 people (26,8%) has less knowledge. While for experience as much 95 people (97,9%) has good experience and 2 people (2,1%) has bad experience. Suggested to menopausal woman to find level of knowledge and experience hot flashes. Keywords: experience, hot flashes, knowledge, menopause